1997
DOI: 10.1006/frne.1997.0154
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine Asymmetry

Abstract: The information available at present clearly indicates that asymmetry exists from the level of elementary particles to the human cerebral cortex, the latest stage of evolution. Cerebral lateralization is one of the well-known asymmetries. This paper summarizes the data published in the past decades on the asymmetry of the neuroendocrine system. The information on the sided-differences between the gonads, adrenals, and thyroid lobes and that on the lateralization of hypothalamic, limbic, and other brain structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
61
1

Year Published

2002
2002
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(68 citation statements)
references
References 114 publications
6
61
1
Order By: Relevance
“…We evaluated both excitatory and inhibitory synaptic physiology in MeApd slices from 25-to 29-dold male and female rats. Previous reports that the MeA is lateralized (Gerendai and Halász, 1997;Cooke et al, 2003) led us to examine the left and right MeApd slices separately.…”
Section: Functional Sex Differences In the Meapdmentioning
confidence: 99%
“…We evaluated both excitatory and inhibitory synaptic physiology in MeApd slices from 25-to 29-dold male and female rats. Previous reports that the MeA is lateralized (Gerendai and Halász, 1997;Cooke et al, 2003) led us to examine the left and right MeApd slices separately.…”
Section: Functional Sex Differences In the Meapdmentioning
confidence: 99%
“…Our prediction is that animals showing greater fluctuating asymmetry and/or with larger adrenal glands, testes and seminal vesicles relative to body size will show greater intensities. We also included right -left asymmetry in adrenal gland weight as an independent variable because studies have suggested an association between directional (left-biased) asymmetry in adrenal gland size and dysfunction of the hypothalamic -pituitary -adrenal hormone axis (Szigethy et al, 1994;Abramov et al, 1996;Gerendai & Halasz, 1997), with greater asymmetry being associated with reduced production of glucocorticoids (Abramov et al, 1996;M. Moshkin, personal communication).…”
Section: Anatomical and Morphometric Predictors Of Parasite Intensitymentioning
confidence: 99%
“…It has been reported that unilateral posterior deafferentation of the hypothalamus on the left side induces a significant decrease in the basal mitosis of the thyroid follicular cells in the left and right lobes and prevents the hemithyroidectomy-induced increase in mitotic activity of follicular cells in the remaining lobe (Lewinski et al, 1982;Gerendai and Halasz, 1997). Therefore, pathways to and from the hypothalamus may exhibit a functional asymmetry in the control of the proliferation of thyroid follicular cells, which affects the thyroid size (Gerendai and Halasz, 1997). The actual reason for the association of handedness with thyroid asymmetry is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Various kinds of asymmetry, including morphological, biochemical, functional, and pathological, exist in the central nervous system (CNS)-target endocrine gland system (Gerendai and Halasz, 1997). In humans, the right testis is heavier and has a higher position than the left testis (Cholst, 1947).…”
mentioning
confidence: 99%
See 1 more Smart Citation